High Expression of CEMIP Correlates Poor Prognosis and the Tumur Microenvironment in Breast Cancer as a Promisingly Prognostic Biomarker - Dong, Xingxing; Yang, Yalong; Yuan, Qianqian; Hou, Jinxuan; Wu, Gaosong (Frontiers in Genetics, 2021)
Cell migration inducing hyaluronidase 1 (CEMIP), a Wnt-related protein and also known as KIAA1199, is implicated in the process of metastatic colonization in a variety of malignant tumors, including breast cancer (BC), which is one of the most frequently diagnosed tumors in women worldwide. In this study, multiple public databases, online analytical tools, and bioinformatics approaches were applied to explore the expression levels, regulatory mechanisms, biological functions of CEMIP in BC. We illustrated that CEMIP was highly expressed in various kinds of carcinomas, including BC, especially advanced subtypes, and predicted less-favorable prognosis (negatively associated with overall survival) in BC patients and might be an independent prognostic factor. Then, we revealed that the mutation and high expression of CEMIP might lead to it as an oncogene. We also demonstrated that TP53 mutation, DNA hypo-methylation, and the expression changes of three potential upstream transcription factors (EZH2, EGR1, and JUN) of CEMIP were likely to cause the hyperexpression of CEMIP in BC. Moreover, our findings suggested that CEMIP might exert its carcinogenic roles in the tumor microenvironment via participating in the extracellular matrix formation, increasing cancer-associated fibroblast (CAF), M2 macrophage, and neutrophil infiltration, and decreasing CD8+ T cell infiltration. In summary, our study provided more solid evidence for CEMIP as a prognostic and metastatic biomarker, and a potential therapeutic target in BC. Of course, these findings also need more confirmations of basic experiments and further clinical trials in the future.